Teaching Coding Using Scratch to Elementary Students: Exploration of Benefits for Students - Nur Fitria, Tira (Journal of Contemporary Issue in Elementary Education, 2025)
In the ever-evolving digital era, knowledge and skills in informatics are becoming more crucial. To equip the younger generation for future challenges, education should integrate technology into its curriculum such as coding programs to foster students' interests and talents in programming and technology. This research describes how coding is taught at the elementary school level and the benefits obtained from implementing coding based on existing research. This research is library research. Currently, many elementary schools in Indonesian Elementary schools are starting to teach coding as a lesson in the official curriculum and as an extracurricular activity. As technology advances and the importance of digital skills in the 21st century, many schools may realize that teaching coding early can help students develop computational thinking, creativity, and problem-solving skills that are important for their future. The finding shows the use of coding especially Stracth in elementary students. Scratch has become a popular tool in teaching programming to children at the elementary school level. Scratch is a visual programming tool designed to introduce programming concepts, especially to children, to train computational thinking in beginners. Scratch allows students to learn programming without having to master complex programming languages. Using Scratch in learning coding has been proven to provide many benefits for students. Scratch helps improve computational thinking skills, programming understanding, and creativity. Scratch also helps students practice problem-solving strategies, accuracy, and critical thinking. In addition, students can create animations and games after taking part in the training, with the support of the important surrounding environment. Scratch supports interactive and fun learning, makes it easier to understand programming logic, and improves basic programming competencies. Overall, Scratch is effective in developing students' technology skills in an engaging and easy-to-understand way.